2012
DOI: 10.1002/pri.1526
|View full text |Cite
|
Sign up to set email alerts
|

Combined Resistance and Aerobic Exercise is Better than Resistance Training Alone to Improve Functional Performance of Haemodialysis Patients — Results of a Randomized Controlled Trial

Abstract: Although the best protocol of exercise for patients on dialysis is not yet clear, in our sample of haemodialysis patients the combination of aerobic and resistance training was more effective than resistance training alone to improve functional performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 36 publications
(56 reference statements)
9
46
2
6
Order By: Relevance
“…The patients usually cycle for 10-45 min and progressively resistance is applied to the bicycle wheels [72][73][74][75][76][77][78][79][80][81][82]. Also, resistance exercises have been applied in intradialytic exercise training programs without serious complications and induced beneficial effects on patient's muscular strength [83][84][85][86][87][88][89][90] The exercises sessions occurred at the hemodialysis centers during the first two hours of the hemodialysis treatment (table 4). According to Moore et al [41] is more safe exercise training programs to be applied during the first 2 hours because cardiac function is more stable.…”
Section: Effects Of Intradialytic Exercise Programsmentioning
confidence: 99%
“…The patients usually cycle for 10-45 min and progressively resistance is applied to the bicycle wheels [72][73][74][75][76][77][78][79][80][81][82]. Also, resistance exercises have been applied in intradialytic exercise training programs without serious complications and induced beneficial effects on patient's muscular strength [83][84][85][86][87][88][89][90] The exercises sessions occurred at the hemodialysis centers during the first two hours of the hemodialysis treatment (table 4). According to Moore et al [41] is more safe exercise training programs to be applied during the first 2 hours because cardiac function is more stable.…”
Section: Effects Of Intradialytic Exercise Programsmentioning
confidence: 99%
“…3 Aqui no Brasil, alguns grupos de estudos realizam pesquisa com esta população. Entre eles, destaco o trabalho realizado por Orcy et al, 4 enfatizando a associação do EAI com o treinamento de força para a melhora da capacidade funcional dos pacientes, encontrando aumento significativo na distância percorrida no teste de caminhada pelos pacientes após 10 semanas de treinamento. Reboredo et al 5 avaliaram os efeitos do EAI na pressão sanguínea, capacidade físi-ca e qualidade de vida nos pacientes por 12 semanas e também encontraram aumento significativo na distância percorrida no teste de caminhada, redução nas pressões arterial sistólica, diastólica e média, aumento nos valores séricos de hemoglobina e melhora nas dimensões física, social e saúde mental no questionário SF-36.…”
Section: Prezado Editorunclassified
“…Twelve trials prescribed lower body exercises only [26, 27, 30-32, 36-41, 43-48], while 4 trials prescribed both upper-and lower body exercises [20,28,29,35] . All studies prescribed 2-3 sessions of PRT per week, and 1-5 sets per exercise.…”
Section: Prt Interventionsmentioning
confidence: 99%
“…The mean age of participants ranged from 42.8 to 70 years. All trials were open to both men and women; however, 2 studies recruited no women [29,32] , and one article reported on a subgroup of men only [44] .…”
Section: Descriptive Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation